DETERMINAÇÃO DE CÁDMIO E CHUMBO EM BIODIESEL POR VOLTAMETRIA DE PULSO DIFERENCIAL E DE REDISSOLUÇÃO ANÓDICA USANDO ELETRODO DE FILME DE BISMUTO EM MEIO ETANÓLICO - Guimarães, Myrna Barbosa (2011)
This work presents a simple procedure based on technique anodic stripping voltammetry (ASV) to determine Cd2+ and Pb2+ in Biodiesel (B100), without prior sample treatment, using a bismuth film electrode (BiFE), prepared as ex situ mode. Samples were simply diluted into a 0.1 mol L-1 acetate buffer ethanolic (pH 4.5), being the pH apparent (pH*) adjusted with HCl 1 mol L-1 before analysis. This intended to provide the conversion of the analytes to their inorganic forms. After optimization of the voltammetric and experimental conditions, the parameters ideal values for the determination of these metals were obtained as following: deposition potential: -1.4 V; deposition time: 180 s; scan rate: 25 mV s-1; modulation amplitude: 50 mV; pH apparent (pH*) ~ 2.0. The voltammograms and their corresponding standard analytical curves indicated that BiFE associated with ASV in the diferential pulse mode (DPASV) provide useful and sensitive procedure for determination of metal in B100 at trace level. The results showed a linear response between current and concentration of Cd2+ and Pb2+ ions. Adequates detection limits (3s, n = 5) were obtained for Cd2+ (1.71x10-8 mol L-1) and Pb2+ (1.92x10-9 mol L-1) for the analysis of B100. The accuracy was assessed by the recovery test (recoveries of 97 to 100 % for Cd2+ and 87 to 107 % for Pb2+). The precision expressed by coefficient of variation was less than 10 % for Cd2+ and less than 7 % for Pb2+. The method was applied successfully to four different biodiesel samples analyzed in triplicate. Pb2+ was quantified in three samples while Cd2+ only was found in two of the four analysed samples. The procedure showed good analytical results for a 95% of confidence level.